Isospora machadoae sp. nov. (Protozoa: Apicomplexa: Eimeriidae), a new coccidian species from white-necked thrushes Turdus albicolis (Passeriformes: Turdidae) of South America - Irlane F. de Pinho; Lidiane M. da Silva; Mariana B. Rodrigues; Bruno do B. Lopes; Mariana S. Oliveira; Hermes R. Luz; Ildemar Ferreira; Carlos Wilson G. Lopes; Bruno P. Berto (Zoologia (Curitiba), 2018)
ABSTRACT A new coccidian species parasitizing white-necked thrushes Turdus albicollis Vieillot, 1818 is described from the Parque Nacional do Itatiaia, in Southeastern Brazil. Isospora machadoae sp. nov. has oocysts that are sub-spherical, 22.2 × 21.2 µm, with bilayered wall, ~1.3 μm thick. Outer layer is rough with micropyle and micropyle cap. Oocyst residuum is absent, but one or two polar granules are present. Sporocysts are ellipsoidal, 13.3 × 9.7 µm. The Stieda body is flattened to half-moon-shaped and substieda body rounded. Sporocyst residuum is present, composed of scattered spherules of different sizes. Sporozoites are vermiform with a refractile body and a nucleus. These parasitized thrushes had no apparent clinical signs of coccidiosis or high densities of oocysts in feces. This condition may be associated with a specific low pathogenicity of I. machadoae sp. nov. and/or with the conserved habitat of these birds, which ensures the ecological niches and thus the immunocompetence to wildlife.